Multivariate optimization of a two-way technique for extraction of pharmaceuticals in surface water using a combination of membrane assisted solvent extraction and a molecularly imprinted polymer. (January 2022) - Khulu, Sinegugu; Ncube, Somandla; Nuapia, Yannick; Madikizela, Lawrence Mzukisi; Tutu, Hlanganani; Richards, Heidi; Ndungu, Kuria; Mavhunga, Elizabeth; Chimuka, Luke
Abstract: This work demonstrates development and evaluation of a two-way technique based on the combination of membrane assisted solvent extraction and a molecularly imprinted polymer (MASE-MIP) for selective and efficient extraction of five selected pharmaceuticals belonging to five different therapeutic classes. The pharmaceuticals were extracted from surface water samples followed by liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-qTOF/MS) determination. A central composite design was applied to optimize the influence of the sample salt content, the stirring rate, the stirring time and the amount of MIP on the extraction of an anticonvulsant (carbamazepine), a cardiac stimulant (etilefrine), a muscle relaxant (methocarbamol), an antiretroviral (nevirapine) and an antidepressant (venlafaxine) from surface water. Optimization of the analytical method was performed by spiking water with a mixture of all five pharmaceuticals at 500 ng mL −1 . Optimum extraction conditions for a sample volume of 18 mL were found to be 5 g of salt content, a stirring rate of 400 rpm, an extraction time of 60 min and 50 mg of MIP. The MASE-MIP-LC-qTOF/MS method gave detection and quantification limits ranging from 0.09 to 0.20 ng mL −1 and 0.31–0.69 ng mL −1, respectively. The spiked river water samples yielded recoveries ranging from 38 to 91% for the selected model compounds belonging to the five classes of pharmaceuticals. Upon the application of the developed analytical method in water analysis, all selected pharmaceuticals were detected in South African river water with nevirapine and venlafaxine being more prominent attaining the maximum concentrations of 1.64 and 2.48 ng mL −1, respectively. Graphical abstract: Image 1 Highlights: A MASE-MIP technique was developed for monitoring pharmaceuticals in water samples. Optimization of the analytical method was done using a central composite design. Good experimental and statistical method performances were observed. Method was applied in extraction of 5 pharmaceutical classes in river water. Nevirapine (1.64 ng mL −1 ) and venlafaxine (2.48 ng mL −1 ) were more prominent.